A növények élettani állapotának hatása a nekrotróf és a biotróf kórokozó fertőzésekre adott válaszaira - Barna, Balázs; Máté, Gabriella; Manninger, Sándorné (GEORGIKON FOR AGRICULTURE, 2017)
It has been known since a long time that the physiological state of plants has a strong influence on their resistance to pathogens. Generally biotrophic pathogens prefer young, while necrotrophic pathogens prefer senescent plant tissues. Accordingly, culture discs of the necrotroph Alternaria alternata caused large yellow and necrotic flecks on old tobacco leaves, but these symptoms could hardly be seen after Alternaria infection on young leaves. Hypersensitive symptoms caused by the hemibiotroph Pseudomonas syringae avirulent bacteria were also suppressed in young leaves as compared to old ones, but in compatible tobacco-bacteria interaction the symptoms were similar on old and young leaves. Infection with races 12 or 61 of the biotroph wheat leaf rust showed always more uredospore colony numbers on first leaves in first leaf stage, than on third leaves of all six tested wheat, but especially of Mv C1535-02 and MV Emma genotypes. It would be of great importance in the breeding practice, if we could test wheat adult plant resistance against rust in early, three leaf stage, but it needs confirmation by field experiments.